Performance and yield of several sweet corn varieties suitable for animal feed / Muhammad Azhar Zulkffle, Assoc. Prof. Dr. Zakaria Mat Arof and Roslinda Ismail - Zulkffle, Muhammad Azhar; Mat Arof, Zakaria; Ismail, Roslinda (Research Management Institute, 2011)
Maize is an essential source of multi-nutrients plant used as supplement in rudimentary livestock diets. However, until now there is no specific maize variety that has been adopted for that purpose in Malaysia. This situation could result in reduced efficiency in livestock industry as the low nutrient content in animal diet could impede animal growth and meat production. This study focus on analyzing several maize varieties micro and macronutrient content by using ICPMS (Inductively coupled plasma mass spectrometry) to screen the best maize variety that contain acceptable level of nutritive value suitable to be use in animal feed. All method and samples analyzed using ICPMS were done at Agriculture Chemical Analysis Laboratory (D10),Mardi Serdang. Regarding maize plantation plot, experiment was conducted in UiTM Perlis Farm where the maize varieties were planted in one large plot (approximately 0.4 hectare) consisting 7-8 rows of maize. The maize was planted in large plots with common agronomy practices (as practice by UiTM Perlis Farm's Unit). Result of the study has shown that corn variety A (Taiwan) has approximately 11.77% crude protein, 4745.52 cal/gm gross energy, 8.52% crude fiber and 1.88% N. As for maize variety B (Korea), the crude protein is 10.87%, gross energy 4786.08 cal/gm, 11.66% crude fiber and 1.74% N. Both corn varieties consist different percentage of major and trace elements such as Al, Ca, Cu, Fe, K, Mg, Na, P, S and Zn which is beneficial to livestock diet. From study, maize variety A (Taiwan) shows extra advantage relatively compared to maize variety B (Korea). Maize A shows higher percentage of CP, DM and several trace minerals, which is important for animal. Maize B show higher percantage on several fiber component such as ADF, lignin and NDF which help in digestion for animal. It also shows that sweet corn varieties as used in this study have a complete set of nutrients that suitable for not only human but also for animal feed (livestock). During December, which have high rainfall (avetage >220 mm) and low temperature (average 28 °C and >90% RH),corn planting areas might be affected by fungus (mildrew), heavy rain can cause fertilizer drain to unwanted area and not suitable to start planting corn and other crops.